Preparation method and application of wood extract-based porous material

By preparing lignin-based porous materials with appropriate pore size and porosity, combined with fertilizers to control the slow release rate, the problem of low fertilizer utilization is solved, effective slow release of fertilizers and reduced environmental pollution is achieved, and in various environments, it is also possible to achieve effective slow release of fertilizers and reduce environmental pollution. Maintain durability under conditions.

CN119119557AInactive Publication Date: 2024-12-13YUNCHENG TIANWO BIOLOGICAL FERTILIZER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411243055.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The low utilization rate of existing chemical fertilizers leads to the release of fertilizers too quickly and it is difficult for crops to absorb them completely, resulting in an imbalance in fertilizer nutrients and crop demand, which in turn causes environmental pollution problems.

Method used

By preparing lignin-based porous materials with appropriate pore size and porosity, combining fertilizers to control slow release speed, and forming a 3D network structure through a specific ratio of acrylamide to N,N-2-methacrylamide, enhancing lignin Compatibility and binding force with fertilizer reduce crosslinking to expand the pore structure and provide suitable open mesoporous channels.

Benefits of technology

The slow release rate control of fertilizers is achieved, the shelf life is extended, the utilization rate of fertilizers is improved, environmental pollution is reduced, and durable performance is maintained under various environmental conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of slow-release packing materials, and particularly discloses a preparation method and application of a wood extract-based porous material, the wood extract-based porous material obtains proper pore size and porosity by controlling the crosslinking state between lignin and acrylamide polymer, and can provide a channel for fertilizer release after being combined with fertilizer, so that the fertilizer release rate is increased, and the fertilizer release rate is increased. And the slow release speed of the fertilizer is controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sustained-release packaging materials, and specifically relates to a preparation method and application of a lignin-based porous material. Background Art

[0002] Fertilizers play a vital role in increasing crop yields and incomes. The fertilizers currently used on the market have the problem of low crop absorption efficiency, and 30% to 50% of fertilizer nutrients are lost through various channels, resulting in waste. The low utilization rate of fertilizers is bound to lead to excessive fertilizer application, which in turn leads to a series of environmental problems, such as eutrophication of water bodies, groundwater pollution, air pollution, soil degradation, etc. According to the "Second National Pollution Source Census Bulletin", in 2017 alone, the planting industry discharged 83,000 tons of ammonia nitrogen, 719,500 tons of total nitrogen, and 76,200 tons of total phosphorus.

[0003] The fundamental reason for the low utilization rate of chemical fertilizers is that chemical fertilizers are released too quickly and it is difficult for crops to absorb all of them, that is, there is an imbalance between the nutrients released by fertilizers and the needs of crops. Slow-release fertilizers are a type of fertilizer that uses physical and chemical methods to modify ordinary compound fertilizers, giving them a longer release cycle. They can provide nutrients for crops at all growth stages and reduce losses due to leaching and volatilization. They have the advantages of improving fertilizer utilization and reducing environmental pollution caused by excessive fertilization.

[0004] Coated slow-release fertilizer is the main form of physical barrier slow-release fertilizer. Polymer materials commonly used for coating include polyurethane and polysulfone, which are generally difficult to degrade. Natural macromolecules such as lignin are relatively cheap, biodegradable, non-toxic, and help improve soil properties. They are gradually gaining attention in the field of slow-release fertilizer research and development. Patent CN113816794B discloses a method for preparing a lignin-based water-retaining double-layer slow-release fertilizer. The patent grafts acrylic acid-acrylamide copolymer with lignin derivatives to obtain a lignin-based water absorbent as the outer layer of a single-layer coated fertilizer, which makes up for the shortcomings of single-layer coated fertilizers, such as single performance, short slow-release time, and difficulty in control. However, this method may bring about the problem of too slow slow release. Summary of the invention

[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present invention obtains a lignin-based porous material with suitable pore size and porosity by controlling the cross-linking state, which provides a channel for the release of the fertilizer after combining with the fertilizer and controls the slow release rate of the fertilizer.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a method for preparing a lignin-based porous material, comprising the following steps:

[0008] S1, dissolving acrylamide, ammonium persulfate and N,N-2-methylacrylamide in deionized water, stirring for 30-60 minutes and then ultrasonicating for 20-40 minutes to obtain prepolymer 1;

[0009] S2, dissolving lignin in ethyl acetate, adding vinylbenzyl chloride, ethylene glycol dimethacrylate and azobisisobutyronitrile, heating at a speed of 200-400 rpm, and cooling to room temperature to obtain prepolymer 2;

[0010] S3, adding dichloromethane to the prepolymer 2 of step S2, stirring at room temperature for 2-6 hours, heating to 30-50° C., adding anhydrous ferric chloride, stirring for 40-60 minutes and then post-treating to obtain prepolymer 3;

[0011] S4, adding the prepolymer 1 of step S1 to the prepolymer 3 of step S3, stirring for 50-70 minutes, ultrasonicating for 20-40 minutes, pouring into a mold and standing at 50-70° C. for 10-15 hours to obtain the lignin-based porous material.

[0012] The applicant uses the matrix formed by the polymerization of acrylamide to provide a certain rigidity for the lignin-based porous material, so that the slow-release particles formed by the fertilizer and the porous material will not be easily crushed, thereby extending the shelf life.

[0013] Since the interaction between lignin molecules easily leads to agglomeration of lignin, in order to enhance the compatibility of lignin in the acrylamide polymerization process, the applicant initially cross-linked the lignin with vinylbenzyl chloride and ethylene glycol dimethacrylate, which provided better compatibility. However, the applicant found that the lignin-based porous material prepared by this method had the problems of low specific surface area, large and single pore size, which resulted in too fast release of fertilizer.

[0014] To solve this problem, the applicant further cross-linked the lignin, increased the specific surface area and porosity, reduced the pore size, and consumed the -CH2Cl in the initial cross-linking and converted into a rigid methylene cross-linking bridge, making the micropores stable. However, the pore structure constructed by this method is mainly narrow micropores, resulting in a slow mass transfer and diffusion rate of the fertilizer in this pore environment, which reduces the release rate of the fertilizer. In response to this, the applicant reduced the cross-linking degree of the porous material by reacting the amino group with the ester group, expanded the pore structure, and provided an open mesoporous channel of suitable size for the slow release of the fertilizer.

[0015] In some embodiments, the mass ratio of acrylamide to N,N-2-methylacrylamide in step S1 is 1:(0.0006-0.0018).

[0016] The invention forms a 3D interconnected network structure by specifically selecting the dosage of acrylamide and N,N-2-methylacrylamide.

[0017] In some embodiments, the mass ratio of ammonium persulfate to the total content of acrylamide and N,N-2-methylacrylamide in step S1 is (0.0050-0.0054):1.

[0018] In some embodiments, the mass ratio of lignin in step S2 to acrylamide in step S1 is (0.017-0.034):1.

[0019] In some embodiments, the mass ratio of lignin, vinylbenzyl chloride and ethylene glycol dimethacrylate in step S2 is 1:(3.5-4.5):(3-5).

[0020] The applicant found in the study that the initial cross-linking of lignin may lead to a relative decrease in the degree of cross-linking, which may lead to structural collapse under heat drying, mechanical friction or chemical action. In particular, when preparing slow-release particles, the particles will produce internal stress of expansion or contraction. This unbalanced effect will cause the particles to break. The present invention ensures the stability of the body structure by specifically selecting the ratio of lignin, vinylbenzyl chloride and ethylene glycol dimethacrylate.

[0021] In some embodiments, the mass ratio of azobisisobutyronitrile to ethylene glycol dimethacrylate in step S2 is (0.07-0.16):1.

[0022] In some embodiments, the heating operation in step S2 is first stirring at 70-80° C. for 2-4 hours, and then heating to 85-95° C. and stirring for 2-6 hours.

[0023] In some embodiments, the mass ratio of the anhydrous ferric chloride in step S3 to the vinylbenzyl chloride in step S2 is (0.8-1.7):1.

[0024] The present invention enables lignin to be uniformly distributed in the 3D interconnected network structure of the porous material through specific selection of the ratio between the raw materials.

[0025] In some embodiments, the specific steps of post-treatment in step S3 are: first quench the reaction with a 40-50 wt % ethanol aqueous solution, then wash with anhydrous ethanol and water for 2-3 times respectively, and then extract with anhydrous ethanol for 20-25 hours.

[0026] A second aspect of the present invention provides an application of a lignin-based porous material in slow-release fertilizers.

[0027] The present invention adds modified lignin during the polymerization of acrylamide to obtain a material with suitable pore size and porosity. These rich porous structures provide channels for the release of fertilizers and control the slow release rate of fertilizers. In addition, the non-polar benzene ring structure in the porous material enhances its hydrophobicity, while the rich nitrogen oxide groups bring extremely strong hydrophilicity. This hydrophilicity and hydrophobicity can control the dissolution rate of fertilizers and can also maintain excellent durability under various external environmental conditions.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention provides a lignin-based porous material with suitable pore size and porosity, which can provide a channel for the release of fertilizers and control the slow release rate of fertilizers.

[0030] 2. The lignin porous material of the present invention has a certain rigidity, so that the slow-release particles formed by the fertilizer and the porous material will not be easily crushed, thereby extending the shelf life; its hydrophilicity and hydrophobicity can also maintain excellent durability under various external environmental conditions.

[0031] 3. The lignin and acrylamide polymer in the porous material of the present invention have good compatibility, and the binding force between lignin and fertilizer can increase the binding amount of fertilizer. DETAILED DESCRIPTION

[0032] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0033] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments and comparative examples are described as follows:

[0034] Lignin was purchased from Shandong Longli Biotechnology Co., Ltd.

[0035] Example 1

[0036] A method for preparing a lignin-based porous material comprises the following steps:

[0037] S1, dissolving 100 g acrylamide, 0.52 g ammonium persulfate and 0.12 g N,N-2-methylacrylamide in 700 mL deionized water, stirring for 45 min and then ultrasonicating for 30 min to obtain prepolymer 1;

[0038] S2, 2.5 g of lignin was mixed with 100 mL of ethyl acetate, 10 g of vinylbenzyl chloride, 10 g of ethylene glycol dimethacrylate and 1.1 g of azobisisobutyronitrile were added, and the mixture was stirred at 75° C. for 3 h, and then heated to 90° C. and stirred for 4 h at a speed of 300 rpm. After cooling to room temperature, prepolymer 2 was obtained;

[0039] S3, add 240mL of dichloromethane to the prepolymer 2 of step S2, stir at room temperature for 4h, heat to 40°C, add 12.5g of anhydrous ferric chloride, stir for 50min, quench the reaction with 45wt% ethanol aqueous solution until the temperature does not change, then wash with anhydrous ethanol and water for 3 times respectively, and then extract with anhydrous ethanol for 24h to obtain prepolymer 3;

[0040] S4, adding the prepolymer 1 of step S1 to the prepolymer 3 of step S3, stirring for 60 minutes, and after ultrasonication for 30 minutes, pouring into a mold and standing at 60° C. for 12 hours to obtain a lignin-based porous material.

[0041] Example 2

[0042] A method for preparing a lignin-based porous material comprises the following steps:

[0043] S1, dissolving 100 g acrylamide, 0.52 g ammonium persulfate and 0.06 g N,N-2-methylacrylamide in 700 mL deionized water, stirring for 30 min and then ultrasonicating for 40 min to obtain prepolymer 1;

[0044] S2, 1.7 g of lignin was mixed with 85 mL of ethyl acetate, and 5.95 g of vinylbenzyl chloride, 5.1 g of ethylene glycol dimethacrylate and 0.36 g of azobisisobutyronitrile were added, and the mixture was stirred at 70° C. for 4 h, and then heated to 85° C. and stirred for 6 h at a speed of 200 rpm. After cooling to room temperature, prepolymer 2 was obtained;

[0045] S3, add 180mL of dichloromethane to the prepolymer 2 of step S2, stir at room temperature for 2h, heat to 30°C, add 4.76g of anhydrous ferric chloride, stir for 40min, quench the reaction with a 40wt% ethanol aqueous solution until the temperature does not change, then wash with anhydrous ethanol and water twice respectively, and then extract with anhydrous ethanol for 20h to obtain prepolymer 3;

[0046] S4, adding the prepolymer 1 of step S1 to the prepolymer 3 of step S3, stirring for 50 minutes, and after ultrasonication for 40 minutes, pouring into a mold and standing at 50° C. for 15 hours to obtain a lignin-based porous material.

[0047] Example 3

[0048] A method for preparing a lignin-based porous material comprises the following steps:

[0049] S1, dissolving 100 g acrylamide, 0.52 g ammonium persulfate and 0.18 g N,N-2-methylacrylamide in 700 mL deionized water, stirring for 60 min and then ultrasonicating for 20 min to obtain prepolymer 1;

[0050] S2, 3.4 g of lignin was mixed evenly with 118 mL, 15.3 g of vinylbenzyl chloride, 17 g of ethylene glycol dimethacrylate and 2.72 g of azobisisobutyronitrile were added, and the mixture was stirred at 80 ° C for 2 h, then heated to 95 ° C and stirred for 2 h at a speed of 400 rpm, and cooled to room temperature to obtain prepolymer 2;

[0051] S3, add 300 mL of dichloromethane to the prepolymer 2 of step S2, stir at room temperature for 6 h, heat to 50 ° C, add 26 g of anhydrous ferric chloride, stir for 60 min, quench the reaction with 50 wt% ethanol aqueous solution until the temperature does not change, then wash with anhydrous ethanol and water for 3 times respectively, and then extract with anhydrous ethanol for 25 h to obtain prepolymer 3;

[0052] S4, adding the prepolymer 1 of step S1 to the prepolymer 3 of step S3, stirring for 70 minutes, and after ultrasonication for 20 minutes, pouring into a mold and standing at 70° C. for 10 hours to obtain a lignin-based porous material.

[0053] Example 4

[0054] This embodiment provides a method for preparing a lignin-based porous material. The specific implementation method is the same as that of Example 1, except that the amount of N,N-2-methylacrylamide used in step S1 is 0.05 g.

[0055] Example 5

[0056] This embodiment provides a method for preparing a lignin-based porous material. The specific implementation method is the same as that of Example 1, except that the amount of N,N-2-methylacrylamide used in step S1 is 0.2 g.

[0057] Example 6

[0058] This embodiment provides a method for preparing a lignin-based porous material. The specific implementation method is the same as that of Example 1, except that the amount of ethylene glycol dimethacrylate used in step S2 is 2.76 g.

[0059] Example 7

[0060] This embodiment provides a method for preparing a lignin-based porous material. The specific implementation method is the same as that of Example 1, except that the amount of ethylene glycol dimethacrylate used in step S2 is 15 g.

[0061] Performance Testing:

[0062] 1. Mechanical properties test

[0063] The lignin-based porous material obtained in each example was made into a film with a length of 80 mm, a width of 10 mm, and a thickness of 0.2 mm. The tensile strength and tensile strain of the film were tested using a mechanical universal testing machine. The gauge length was fixed at 30 mm, and the speed of the pneumatic clamp was 5 mm / min.

[0064] 2. Porosity test

[0065] The pore volume V of the membrane was determined based on the weight change of the membrane before and after it was soaked in deionized water. 孔 , porosity = V 孔 / (V 孔 +V 膜骨架 ), where V 膜骨架 Obtained by the density of the membrane raw material and the dry film weight.

[0066] 3. Aperture size test

[0067] The maximum pore size of the film was tested using the bubble method.

[0068] The results are shown in Table 1.

[0069] Table 1 Performance test results

[0070] Tensile strength(MPa) Tensile strain (%) Porosity (%) Pore ​​size (μm) Example 1 113.22 4.96 18.77 0.166 Example 2 108.78 4.41 18.14 0.174 Example 3 105.37 4.12 17.62 0.181 Example 4 91.72 6.68 15.48 0.197 Example 5 97.78 6.04 15.96 0.204 Example 6 93.41 6.32 12.12 0.223 Example 7 95.68 6.17 13.49 0.214

[0071] It can be seen from the data in Table 1 that the films made of the lignin-based porous materials of Examples 1-3 have greater tensile strength and suitable porosity and pore size than those of Examples 4-7. It can be seen from Examples 1 and 4-5 that the change in the amount of N,N-2-methylacrylamide will reduce the tensile strength and porosity of the material, which may be due to the fact that the change affects the formation of the internal network structure of the material, thereby causing uneven pore distribution.

[0072] Compared with Example 1, Examples 6-7 change the amount of ethylene glycol dimethacrylate. From the tensile strength and pore size, it can be seen that an improper ratio will reduce cross-linking, thereby leading to reduced tensile strength and larger pore size, which will make the coated fertilizer prone to structural collapse and breakage under the action of external force; it will also cause the fertilizer to be released too quickly.

[0073] The embodiments described above do not impose any form of limitation on the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a lignin-based porous material, characterized in that: The following steps are involved: S1, dissolving acrylamide, ammonium persulfate and N,N-2-methylacrylamide in deionized water, stirring for 30-60 minutes and then ultrasonicating for 20-40 minutes to obtain prepolymer 1; S2, stirring lignin and ethyl acetate evenly, adding vinylbenzyl chloride, ethylene glycol dimethacrylate and azobisisobutyronitrile, heating at a speed of 200-400 rpm, and cooling to room temperature to obtain prepolymer 2; S3, adding dichloromethane to the prepolymer 2 of step S2, stirring at room temperature for 2-6 hours, heating to 30-50° C., adding anhydrous ferric chloride, stirring for 40-60 minutes and then post-treating to obtain prepolymer 3; S4, adding the prepolymer 1 of step S1 to the prepolymer 3 of step S3, stirring for 50-70 minutes, ultrasonicating for 20-40 minutes, pouring into a mold and standing at 50-70° C. for 10-15 hours to obtain the lignin-based porous material.

2. The method for preparing a lignin-based porous material according to claim 1, characterized in that: The mass ratio of acrylamide to N,N-2-methylacrylamide in step S1 is 1:(0.0006-0.0018).

3. The method for preparing a lignin-based porous material according to claim 2, characterized in that: In the step S1, the mass ratio of ammonium persulfate to the total content of acrylamide and N,N-2-methylacrylamide is (0.0050-0.0054):

1.

4. The method for preparing a lignin-based porous material according to claim 1, characterized in that: The mass ratio of lignin in step S2 to acrylamide in step S1 is (0.017-0.034):

1.

5. The method for preparing a lignin-based porous material according to claim 4, characterized in that: In the step S2, the mass ratio of lignin, vinylbenzyl chloride and ethylene glycol dimethacrylate is 1:(3.5-4.5):(3-5).

6. The method for preparing a lignin-based porous material according to claim 5, characterized in that: The mass ratio of azobisisobutyronitrile to ethylene glycol dimethacrylate in step S2 is (0.07-0.16):

1.

7. The method for preparing a lignin-based porous material according to claim 1, characterized in that: The heating operation of step S2 is to first stir at 70-80° C. for 2-4 h, and then heat to 85-95° C. and stir for 2-6 h.

8. The method for preparing a lignin-based porous material according to claim 5, characterized in that: The mass ratio of the anhydrous ferric chloride in step S3 to the vinylbenzyl chloride in step S2 is (0.8-1.7):

1.

9. The method for preparing a lignin-based porous material according to claim 1, characterized in that: The specific steps of post-treatment in step S3 are: first quench the reaction with a 40-50 wt % ethanol aqueous solution, then wash with anhydrous ethanol and water for 2-3 times respectively, and then extract with anhydrous ethanol for 20-25 hours.

10. An application of a lignin-based porous material obtained by the method for preparing a lignin-based porous material according to any one of claims 1 to 9, characterized in that: The lignin-based porous material is used for preparing slow-release fertilizers.